Mental Disorder and Violent Crime: A 20-Year Cohort Study in New York State, 1968-1988 - Steadman, Henry J. ([Verlag nicht ermittelbar], 1993)
The objectives of this study were (1) to compare long-term patterns of violent crime for mentally disordered patients and for prison inmates, and (2) to evaluate the predictive validity of a diagnosis of schizophrenia for subsequent arrests for violent crimes. For purposes of this data collection, violent crimes were defined as including murder, manslaughter, rape, assault, kidnapping, and sodomy. The study analyzed individual state mental hospital patients and inmates of state prisons in New York State over a 20-year span. In the process of obtaining information regarding the individuals, three different areas were focused on: hospital, incarceration, and arrest histories. Variables for hospital histories include inpatient hospitalizations, admission and discharge dates, legal status for all state hospitals through 1988, primary diagnosis for target and most recent admissions, and placements in New York State Department of Correctional Services mental hospitals. Incarceration history variables include time spent in adult state prisons, incarcerations through 1988, and dates of release (including re-entry to community on parole, outright release, or escape). Arrest histories include information on the subject's first adult arrest through 1988 (only the most serious charge for each incident is recorded) and out-of-state arrests, when available. Demographic variables include age, race, and date of birth.